Studi Etnografi: Tantangan dan Peluang Digital Learning Pada Pendidikan Menengah Kejuruan - Uci Suriani; Rahma Fitriyani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study examines the challenges and opportunities of digital learning in Vocational High Schools (PMK) in Palembang City, which is a crucial issue in the context of vocational education. The main problems identified include limited infrastructure, lack of digital skills among teachers, and unequal access to devices for students. The purpose of this study is to explore how digital learning can be effectively integrated into the PMK curriculum. The method used is an ethnographic approach, with data collection through interviews, observations, and documentation analysis in four vocational high schools. The results of the study indicate that despite significant challenges, digital learning offers opportunities to improve students' technological skills and innovation in teaching methods. The conclusion of this study emphasizes the need for support from the government and educational institutions to overcome these challenges, so that digital learning can contribute optimally in preparing students for an increasingly digital world of work.